Caracterização fisiológica e bioquímica de cultivares de feijão submetidos a hipoxia em diferentes fases fenológicas - Costa, Beatriz Gonçalves Pereira (2019)
Common bean (Phaseolus vulgaris L.) is one of the most important leguminous grown in Brazil for human consumption, being an important source of protein, carbohydrates and rich in various minerals. In flooding situation, the availability of oxygen can provide a condition of anoxia or hypoxia. The present work aims to evaluate the behavior of BRSMG-Uai and BRSMGMajestoso cultivars submitted to hypoxia in different phenological phases, analyzing their responses in relation to growth and production, gas exchange, carbohydrate metabolismo and nitrate assimilation. In this way, common bean seeds were sown when they reached the V1 development stage and were transferred to containers containing 40 liters of nutrient solution and constant aeration. With the objective of evaluating the phenological phase of greater susceptibility of common bean to hypoxia in the root system, distinct lots of plants were exposed to a lack of aeration condition in three different phenological phases. After aeration it was restored and the plants were able to reach the end of the productive cycle. Phenological phases V3/V4 (appearance of the third trifoliate leaf), R6 (opening of the first flower) and R7 (appearance of the first pods) were considered. In order to do so, the aeration of the nutrient solution was withdrawn from certain containers, while others were aerated to be used as reference. After 9 days of hypoxia in the phenological phases V3/V4, R6 and R7 6 plant replicates of each treatment were collected for the biochemical and growth analyzes. The experiment was conducted in a completely randomized design. Both cultivars submitted to low oxygen availability presented a reduction in the number of grains, being in V3/V4 the greatest loss in production, giving greater sensitivity to hypoxia in this phase. Reduction in gas exchange in all phenological phases besides the decrease in pigment levels in the cultivar BRSMG-Uai. In the phenological phase R7 the cultivar BRSMG-Majestoso showed increase in the pigment contents. On the other hand, there was an increase in the sugar concentration in the leaves of both cultivars due to the reduced translocation of these photoassimilates to the drains (grains and roots). The cultivar BRSMG-Uai presented in leaves, increase in the content of hydrogen peroxide, whereas the cultivar BRSMG-Majestic presented only increase in phenological phase R6. Both cultivars presented increase in the content of hydrogen peroxide in roots. The decrease of the SOD enzyme activity occurred in the phenological phases V3/V4, R6 and R7 of both cultivars. CAT activity increased only in BRSMG-Majestoso cultivar at R7. On the other hand, the APX enzyme showed increased root activity in the cultivar BRSMG -Uai in R6 and in BRSMG-Majestoso cultivar R7 in leaves and roots. The lipid peroxidation of the cultivar BRSMG-Uai showed increase in leaves and roots of the three phenological phases. In the cultivar BRSMG-Majestic, only V3/V4 presented increase of lipid peroxidation in the leaves and roots. Both cultivars presented increased activity of the Nitrate Reductase enzyme. It was concluded that the cultivar BRSMG-Uai presented greater sensitivity to low oxygen availability, and the phenolic phase V3 / V4 is the most critical for both cultivars submitted to hypoxia.